2007
DOI: 10.1534/genetics.106.067892
|View full text |Cite
|
Sign up to set email alerts
|

Precise Mapping of Quantitative Trait Loci for Resistance to Southern Leaf Blight, Caused by Cochliobolus heterostrophus Race O, and Flowering Time Using Advanced Intercross Maize Lines

Abstract: The intermated B73 3 Mo17 (IBM) population, an advanced intercross recombinant inbred line population derived from a cross between the maize lines B73 (susceptible) and Mo17 (resistant), was evaluated in four environments for resistance to southern leaf blight (SLB) disease caused by Cochliobolus heterostrophus race O. Two environments were artificially inoculated, while two were not inoculated and consequently had substantially lower disease pressure. Four common SLB resistance quantitative trait loci (QTL) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
121
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(140 citation statements)
references
References 49 publications
12
121
3
Order By: Relevance
“…Two linked QTL in the intermated population were identified in a region where a single QTL was detected in the F 3 population. These observations are consistent with those of Balint-Kurti et al (2007) who observed a notable gain in precision in QTL mapping in their intermated population, reaching up to 50-fold smaller CI in the specific situation of breaking linkage of two QTL in repulsion. However, we detected globally fewer QTL in the intermated population than in the conventional one (in the whole data set, we detected slightly more QTL for DGY, but much fewer for the other traits).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Two linked QTL in the intermated population were identified in a region where a single QTL was detected in the F 3 population. These observations are consistent with those of Balint-Kurti et al (2007) who observed a notable gain in precision in QTL mapping in their intermated population, reaching up to 50-fold smaller CI in the specific situation of breaking linkage of two QTL in repulsion. However, we detected globally fewer QTL in the intermated population than in the conventional one (in the whole data set, we detected slightly more QTL for DGY, but much fewer for the other traits).…”
Section: Discussionsupporting
confidence: 91%
“…Because recombination rates were estimated on the basis of the accumulation of recombination events through random mating generations (Lee et al 2002;Winkler et al 2003;Falque et al 2005Falque et al , 2006Falque 2005), the unit of distance in the LHRF-F 3 population does not correspond to ''true'' centimorgans. We designated this unit of distance ''IcM'' for ''intermated centimorgans,'' as reported in the literature (Balint-Kurti et al 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This population has been used to map QTLs for cell wall composition, flowering time, and resistance to southern leaf blight (Hazen et al, 2003;Balint-Kurti et al, 2007). In our analysis, none of the 16 QTLs identified mapped to phytochrome gene family or Elm1 loci.…”
Section: Discussionmentioning
confidence: 93%